2011
DOI: 10.1007/s00296-010-1740-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulsed electromagnetic fields on the mRNA expression of CAII and RANK in ovariectomized rats

Abstract: The present study was designed to determine the effects of pulsed electromagnetic fields (PEMFs) on the mRNA expression of the carbonic anhydrase II (CAII) and receptor activator of NF-κB (RANK) in ovariectomized rats. A total of 48 SD rats were randomly divided into four groups [Sham, OVX, PEMFs, and E(2) (premarin)], 12 rats in each group. Rats in the Sham group received sham ovariectomy, while rats in OVX, PEMFs, and E(2) groups received ovariectomy. Twelve weeks following the surgery, rats (whole body) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Standard ultrasonic coupling gel was applied between the transducer head and the limb to minimize reflection and attenuation of the US energy. Concurrently, rabbits in the ERT group were orally treated with conjugated estrogens tablets (Pfizer, New York, USA) at 0.625 mg/kg/day for 10 days (28,29). The OVX and control groups remained untreated.…”
Section: Animals Were Housed In Individual Cages With a 12:12-h Lightmentioning
confidence: 99%
“…Standard ultrasonic coupling gel was applied between the transducer head and the limb to minimize reflection and attenuation of the US energy. Concurrently, rabbits in the ERT group were orally treated with conjugated estrogens tablets (Pfizer, New York, USA) at 0.625 mg/kg/day for 10 days (28,29). The OVX and control groups remained untreated.…”
Section: Animals Were Housed In Individual Cages With a 12:12-h Lightmentioning
confidence: 99%
“…As shown by clinical evidence, therapeutic effects can be achieved for union-delayed and nonunion bone fractures using PEMF treatment at any fracture location. As we previously reported [25], PEMF reduces the gene expression of RANK, CA II and NAFT2 in vitro. A study found PEMF affect only the osteoclast phenotype after short exposure times [42].…”
Section: Figurementioning
confidence: 66%
“…PEMF stimulation for 30 days restored trabecular bone mass of PEMF+OVX rats to levels equivalent to agematched intact rats. We have previously reported that PEMFs applied at 3.8 mT, 8 Hz, for 40 min per day could regulate osteoclast gene expression of CA II and RANK in vivo and in vitro [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed electromagnetic fields (PEMF) have been proven to present satisfying therapeutic effects on OP experimentally and clinically 9, 12, 37, 38 . However, the potential mechanism responsible for the effects of PEMF on preservation of bone mass are not well understood.…”
Section: Discussionmentioning
confidence: 99%